Room-temperature shape memory piezoelectric polymer composite bridge joint filling material as well as preparation method and application thereof
Through the development room temperature -shaped memory polymer composite bridge filling material, the interoperability of epoxy resin, thermoplastic polyurethane and piezoelectric ceramics can be used to solve the problem of matching and insufficient displacement adaptability of the bridge telescopic seams. The efficient adaptive shape memory and stability of the bridge are achieved.
Patent Information
- Application Number
- CN202411539189.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing bridge expansion joint caulking materials have problems such as low matching with the bridge structure and poor displacement adaptability, resulting in low bridge stability and safety.
Develop a room temperature -shaped -based memory polymer composite bridge filling material. By mixing the epoxy resin prefabricated with thermoplastic polyurethane prefabricated, it forms a network structure and combines with piezoelectric ceramic materials and conductive agents to achieve the shape of the shape Memory reply.
This material can achieve shape memory recovery at room temperature, improve the adaptiveness of bridge telescopic seam displacement, and enhance the stability and safety of the bridge.
Smart Images

Figure CN119371811A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bridge filling materials, and in particular relates to a room temperature shape memory piezoelectric polymer composite bridge filling material and a preparation method and application thereof. Background Art
[0002] As an important part of the bridge structure, the bridge expansion joint is located at the bridge end joint. Its main function is to adjust the displacement and deformation between the superstructures caused by temperature changes, vehicle loads and bridge construction materials. Its quality directly affects the overall performance and service life of the bridge. In recent years, with the continuous improvement of economic level and the increasing complexity of traffic flow, bridges have gradually developed towards long-term development, and a large number of high-grade highways and super-large highway bridges have been built one after another, which has put forward higher requirements on the stability of bridge expansion joints. At present, most of the bridge expansion joint filling materials have the problems of poor matching with the bridge structure and poor displacement adaptability, which makes the bridge stability and safety low. Therefore, the development of bridge expansion joint filling materials with good durability and large displacement recovery to solve the problems of insufficient adaptive bridge deformation capacity and mismatch between expansion and contraction and bridge deformation has become one of the hot spots in the field of bridge expansion joint research.
[0003] The shape memory effect is that under certain conditions, the material is given a certain shape (initial state), and when the external conditions change, the shape can be changed accordingly and fixed (deformed state). If the external environment changes again in a specific way and pattern, it can be reversibly restored to the initial state, thus completing the cycle of "memory initial state-fixed deformed state-restore initial state". Obviously, materials with shape memory effect can flexibly switch between temporary shape and memory state as the external environment changes. If the bridge expansion joint material is given a certain shape memory effect, it can effectively solve the problem of mismatch between the bridge expansion joint filling material and the bridge deformation and poor deformation displacement adaptation.
[0004] The prior art discloses polymer bridge gap filling materials which, despite having excellent mechanical properties, lack the property of adaptively adapting to bridge deformation. Summary of the invention
[0005] In view of the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a room temperature shape memory piezoelectric polymer composite bridge caulking material and a preparation method and application thereof. The present invention first separately prepares an epoxy resin precursor and a thermoplastic polyurethane prepolymer containing a reversible dynamic covalent disulfide bond, and then mixes the epoxy resin precursor and the thermoplastic polyurethane prepolymer so that the molecular chains of the two penetrate each other to obtain a polyurethane-epoxy resin with an interpenetrating network structure; and then obtains a chemical formula of (Ba 0.85-2x Li x Al x Ca 0.15)(Zr 0.1 Ti 0.9 )O3 of piezoelectric ceramic material with piezoelectric properties, after mixing the piezoelectric ceramic material, polyurethane-epoxy resin and conductive agent, a room temperature shape memory piezoelectric polymer composite bridge caulking material is obtained. In the room temperature shape memory piezoelectric polymer composite bridge caulking material prepared by the present invention, a polyurethane-epoxy resin containing a reversible dynamic covalent disulfide bond is used as a matrix material, a piezoelectric ceramic material is used to generate electric charge under the action of external stress, and a conductive agent is used as a medium for electrical and thermal conversion, so as to realize the conversion of mechanical energy obtained by road vibration into electrical energy and then into thermal energy, and the thermal energy directly acts on the polyurethane-epoxy resin to increase the breaking, decomposition and recombination of the disulfide bond, and the rapid dynamic exchange reaction causes the network topology to rearrange, so as to promote the shape memory recovery of the room temperature shape memory piezoelectric polymer composite bridge caulking material at room temperature, thereby overcoming the defect that the prior art polymer bridge caulking material lacks adaptive bridge deformation.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a room temperature shape memory piezoelectric polymer composite bridge gap filling material comprises the following steps:
[0008] In a nitrogen atmosphere, after epoxy resin and 2,2'-diaminodiphenyl disulfide are mixed, the amino group of 2,2'-diaminodiphenyl disulfide and the epoxy group of the epoxy resin undergo a ring-opening reaction to obtain an epoxy resin precursor, and a reversible dynamic covalent disulfide bond is introduced into the epoxy resin precursor using 2,2'-diaminodiphenyl disulfide as a raw material. The epoxy resin is a bisphenol A epoxy resin, model E51; the reason for using bisphenol A epoxy resin as a raw material is: a. Compared with other types of epoxy resins, bisphenol A epoxy resin is the epoxy resin with the largest output and the most widely used A variety that is cheap and easy to obtain; b. The molecular structure of bisphenol A epoxy resin contains a bisphenol A skeleton, which gives it good heat resistance. Among them, the average epoxy value of E51 is 51, its viscosity is low, and its hardness after curing is high. It is more suitable for improving the mechanical properties of room temperature shape memory piezoelectric polymer composite bridge filling materials. Therefore, E51 bisphenol A epoxy resin is selected; c. High-purity bisphenol A epoxy resin has low impurity content, low active content, low hydroxyl content, low viscosity and high epoxy content. In practical applications, it has good stability, good chemical corrosion resistance and high mechanical strength.
[0009] In a nitrogen atmosphere, 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide are mixed, and then prepolymerized and chain-extended to obtain a thermoplastic polyurethane prepolymer.
[0010] In a nitrogen atmosphere, an epoxy resin precursor and a thermoplastic polyurethane prepolymer are mixed so that the molecular chains of the epoxy resin precursor and the thermoplastic polyurethane prepolymer penetrate each other to obtain a polyurethane-epoxy resin with an interpenetrating network structure.
[0011] According to the chemical formula (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 weigh Ba source, Li source, Al source, Ca source, Zr source and Ti source, and mix them to obtain a raw material mixture, wherein 0<x<0.3; the Ba source is selected from BaCO3 (purity ≥99%), the Li source is selected from Li2CO3 (purity ≥98%), the Al source is selected from Al2O3 (purity ≥95%), the Ca source is selected from CaCO3 (purity ≥99%), the Zr source is selected from ZrO2 (purity ≥99%), and the Ti source is selected from TiO2 (purity ≥98%).
[0012] The raw material mixture is first pre-calcined at 1200°C-1250°C for 4h-6h to obtain pre-calcined powder I. The pre-calcined powder I is ball-milled and then sieved through a 120-mesh sieve to obtain pre-calcined powder II with a particle size of 0.062mm-0.125mm. The pre-calcined powder I is ball-milled to promote the compatibility of the pre-calcined powder I with the polyurethane-epoxy resin. The pre-calcined powder II is polarized under a DC electric field of 1kV / cm-3kV / cm for 10min-30min to orient its internal electric domains, thereby improving the polarization strength and obtaining a piezoelectric ceramic material with piezoelectric properties.
[0013] Piezoelectric ceramic material, polyurethane-epoxy resin and conductive agent are mixed, and then cast and cured to obtain room temperature shape memory piezoelectric polymer composite bridge filling material; the piezoelectric ceramic material generates electric charge under the action of external stress, and the conductive agent converts the electrical energy into thermal energy. The thermal energy promotes the dynamic covalent bonds of the polyurethane-epoxy resin to break, decompose and recombine, and the rapid dynamic exchange reaction causes the network topology to rearrange, causing it to recover shape memory.
[0014] The conductive agent is selected from conductive carbon black, acetylene black, carbon nanotubes or graphene.
[0015] Preferably, the ring-opening reaction is carried out under the conditions of heating and stirring at 110° C.-130° C. for 2 h-4 h.
[0016] Preferably, the molar ratio of the epoxy group of the epoxy resin to the amino group of 2,2'-diaminodiphenyl disulfide is 1.9-2.0:1.
[0017] Preferably, the conditions for the prepolymerization and chain extension reaction are: heating and stirring at 110° C.-130° C. for 2 h-4 h.
[0018] Preferably, the molar ratio of 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide is 3:1:1.8-2.0. If the ratio is not within this range, the mechanical properties and thermal stability of the thermoplastic polyurethane prepolymer will decrease.
[0019] Preferably, the conditions for mixing 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide are: heating and stirring at 110° C.-130° C. for 2 h-6 h.
[0020] Preferably, the mass percentages of the polyurethane prepolymer and the epoxy resin precursor are 55%-65% and 35%-45% respectively, and the sum of the mass percentages of the two is 100%. If the amount of the polyurethane prepolymer is too high, the toughness of the polyurethane-epoxy resin will be enhanced, and the mechanical properties will be greatly reduced, and the conditions for the use of the bridge expansion joint cannot be met. If the amount of the epoxy resin precursor is too high, the toughness will be greatly reduced, and the glass transition temperature will be too high, resulting in a decrease in the adaptive bridge deformation ability of the polyurethane-epoxy resin in the range of room temperature-60°C.
[0021] Preferably, the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin and conductive agent are 5%-40%, 59.2%-94.8% and 0.2%-0.8% respectively, and the sum of the mass percentages of the three is 100%. Too high a ceramic content will cause the polyurethane-epoxy resin to introduce too many defects, and the mechanical properties will be significantly reduced. If the ceramic content is too low, the piezoelectric performance is poor, and it is difficult to drive the room temperature shape memory piezoelectric polymer composite bridge filling material to undergo shape memory recovery; if the conductive agent content is too low, a complete conductive path cannot be formed inside, and the electrical energy cannot be fully converted into heat energy. If the conductive agent content is too high, the polyurethane-epoxy resin will introduce too many defects, and the mechanical properties will be significantly reduced.
[0022] Preferably, the curing method is: first degassing in a vacuum oven to completely eliminate bubbles, then aging at 60°C-90°C for 10h-24h, and then curing at 100°C-130°C for 4h-8h.
[0023] The present invention also protects the room temperature shape memory piezoelectric polymer composite bridge gap filling material prepared by the above preparation method, and the room temperature shape memory piezoelectric polymer composite bridge gap filling material has shape memory properties at room temperature.
[0024] The invention also protects the use of the room temperature shape memory piezoelectric polymer composite bridge filling material in the preparation of the bridge filling material.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention develops a room-temperature shape memory piezoelectric composite bridge filling material, which converts the mechanical energy generated in the pavement structure into electrical energy. The conversion of electrical energy into thermal energy is achieved by constructing an internal network structure of the room-temperature shape memory piezoelectric composite bridge filling material, thereby promoting shape memory recovery at room temperature, and can effectively improve the adaptability of the displacement of the bridge expansion joint.
[0027] The present invention uses epoxy resin and 2,2'-diaminodiphenyl disulfide as raw materials, and prepares an epoxy resin precursor based on a ring-opening reaction between the amino group of 2,2'-diaminodiphenyl disulfide and the epoxy group of the epoxy resin; in addition, by using 2,2'-diaminodiphenyl disulfide as a raw material and introducing a reversible dynamic covalent disulfide bond, the epoxy resin precursor is endowed with certain self-healing properties.
[0028] The present invention uses 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide as raw materials to prepare a thermoplastic polyurethane prepolymer. By introducing asymmetric ortho-substituted aromatic disulfide 2,2'-diaminodiphenyl disulfide into the main chain, the composition ratio of the soft segment and the hard segment of the thermoplastic polyurethane prepolymer is successfully regulated, and a reversible dynamic covalent disulfide bond is introduced. In terms of regulation, the soft segment is a flexible segment in the thermoplastic polyurethane prepolymer, which is composed of polyether polyol. The soft segment has good flexibility and can improve the flexibility and wear resistance of the thermoplastic polyurethane prepolymer. The molecular weight and crystallinity of the soft segment have a significant effect on the performance of the thermoplastic polyurethane prepolymer; the hard segment is a rigid segment in the polyurethane, which is composed of 4,4-diphenylmethane diisocyanate. Compared with other alicyclic isocyanates, 4,4-diphenylmethane diisocyanate can form a stronger chemical bond, thereby improving the strength and durability of the thermoplastic polyurethane prepolymer. By regulating the mass of chain extender 2,2'-diaminodiphenyl disulfide and 4,4-diphenylmethane diisocyanate, the average length of the chain segments composed of 4,4-diphenylmethane diisocyanate and chain extender 2,2'-diaminodiphenyl disulfide in the hard segment can be controlled, thereby changing the mass fraction of the hard segment, significantly affecting the structure of the soft and hard segments of the thermoplastic polyurethane prepolymer, thereby regulating the performance of the polyurethane.
[0029] The reason for using polyether polyol as raw material is that compared with other polyols, polyether polyol has good hydrolysis resistance and can better adapt to the use environment of bridge expansion joints. In addition, polyether polyol has high reactivity, abundant raw material sources and low price, which makes it more suitable as a filling material and can be used on a large scale in bridge expansion joints. The reason for using 4,4-diphenylmethane diisocyanate as raw material is that 4,4-diphenylmethane diisocyanate has lower toxicity than other isocyanate materials, which can reduce the adverse effects on the environment during large-scale construction and use.
[0030] An epoxy resin precursor is mixed with a thermoplastic polyurethane prepolymer so that their molecular chains interpenetrate each other to obtain a polyurethane-epoxy resin interpenetrating network with an interpenetrating network structure. The interpenetrating network is a new type of polymer formed by the physical entanglement of two or more polymers. This unique interpenetrating penetration and intermolecular entanglement enables the excellent performance of each component to be synergistically blended, so that the interpenetrating polymer network exhibits excellent performance characteristics; when two homopolymers are simply mixed without any molecular entanglement, two different glass transition temperatures are observed, but in the interpenetrating polymer network, it usually has a single wide glass transition temperature, which can be effectively applied to vibration damping and energy absorption. The present invention makes the polyurethane-epoxy resin contain reversible dynamic covalent disulfide bonds through structural design, giving the polyurethane-epoxy resin excellent shape memory properties, and based on the effect of the disulfide bonds, the polyurethane-epoxy resin has good mechanical properties and can achieve rapid self-repair at 80°C.
[0031] 3. The piezoelectric ceramic material (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3, carbonates (BaCO3 (99%), Li2CO3 (98%), CaCO3 (99%)) and oxides (Al2O3 (95%), ZrO2 (99%), TiO2 (98%)) were used to directly prepare barium titanate-based solid solution systems (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3. Prepared (Ba 0.85- 2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 ceramics are at a quasi-modular phase boundary where rhombohedral and orthorhombic coexist at room temperature. In the piezoelectric ceramic materials with perovskite structure, the orthorhombic phase has 12 polarization directions and 180°, 90°, 60°, and 120° domain structures, while the rhombohedral phase has 8 polarization directions and 180°, 71°, and 109° domain structures. Obviously, the ceramic materials at the quasi-modular phase boundary where rhombohedral and orthorhombic coexist can obtain more switchable polarization directions and non-180 domain walls, which effectively reduces the Gibbs free energy barrier and improves the piezoelectric properties of the ceramic materials at room temperature; further, Li + and Al 3+The depolarization electric field generated by spontaneous polarization effectively inhibits the nucleation of antiphase domains, which is beneficial to the improvement of the piezoelectric constant of the material. The piezoelectric constant d33 of the obtained piezoelectric ceramic material can reach 448pC / N at room temperature, and its depolarization temperature can reach 85℃-95℃.
[0032] 4. The present invention combines polyurethane-epoxy resin, conductive agent and piezoelectric ceramic material (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3, and then poured and cured to obtain a room temperature shape memory piezoelectric polymer composite bridge filling material, in which polyurethane-epoxy resin as a matrix material not only ensures the mechanical properties of the composite material, but also has a certain toughness and recovery deformation; piezoelectric ceramic material (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 gives the composite material certain piezoelectric properties, enabling it to generate charges under the action of external stress, thereby realizing the direct utilization of road vibration energy; the conductive agent, as a medium for electrical and thermal conversion, forms a conductive network inside the composite material, realizing the transmission of charges generated by piezoelectric ceramics under stress, and then converting it into thermal energy and directly acting on the polyurethane-epoxy resin, increasing the decomposition and exchange rate of disulfide bonds, promoting its shape memory recovery at room temperature, and at the same time improving the shape memory and self-healing properties of the composite material through the formation of an internal interpenetrating network structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the XRD diagram of the room temperature shape memory piezoelectric polymer composite bridge filling material prepared in Examples 1-4 of the present invention.
[0034] Figure 2 This is the infrared spectrum of the room temperature shape memory piezoelectric polymer composite bridge filling material prepared in Examples 1-4 of the present invention.
[0035] Figure 3 The photographs show the change of the recovery angle over time of the room temperature shape memory piezoelectric polymer composite bridge filling material prepared in Example 4 of the present invention under static and dynamic load conditions.
[0036] Figure 4 This is a diagram of the self-repairing performance of the room temperature shape memory piezoelectric polymer composite bridge filling material prepared in Example 4 of the present invention.
[0037] Figure 5This is a graph showing the change in piezoelectric constant of the piezoelectric ceramic material prepared in Example 1 as the temperature changes. DETAILED DESCRIPTION
[0038] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0039] (1) Piezoelectric materials are an important system of smart materials that can realize the conversion of mechanical energy generated by vehicle load into electrical energy. The present invention provides a piezoelectric ceramic material (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 and its preparation method, piezoelectric ceramic material (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 converts the mechanical energy generated in the pavement structure into electrical energy, and then obtains a room temperature shape memory piezoelectric polymer composite bridge filling material by compounding it with polyurethane-epoxy resin and conductive agent. The internal network structure of the room temperature shape memory piezoelectric polymer composite bridge filling material is constructed to realize the conversion of electrical energy into thermal energy, and then promote shape memory recovery at room temperature, which plays an extremely important role in improving the adaptability of the displacement of bridge expansion joints and the development and application of new materials in the field of smart highways.
[0040] The piezoelectric ceramic material (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 preparation method is simple, repeatable, high yield, and has excellent room temperature piezoelectric properties.
[0041] (2) The room temperature shape memory piezoelectric polymer composite bridge filling material of the present invention has the performance of recovering shape memory at room temperature. Under static load conditions, the recovery rate reaches 47.22%-58.33% at room temperature within 1 minute at a pressure of 1.5 kPa. It can also take into account the self-repairing properties, with a repair rate of 30.5% within 5 minutes at 80°C. It is highly practical, simple to prepare, and easy to mass produce in a routine manner.
[0042] (3) The present invention combines polyurethane-epoxy resin with (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 piezoelectric ceramic materials are compounded. On the one hand, the ceramic powder is evenly dispersed in the polyurethane-epoxy resin with a three-dimensional interpenetrating network structure to form a stable and uniform system; on the other hand, (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 piezoelectric ceramic material is compounded with polyurethane-epoxy resin to obtain a shape memory piezoelectric polymer composite bridge filling material that responds to room temperature, overcoming the shape memory function of shape memory polyurethane-epoxy resin that can only respond under external conditions above 60°C.
[0043] The present invention is further explained by using embodiments below, which are specifically as follows:
[0044] Example 1
[0045] A method for preparing a room temperature shape memory piezoelectric polymer composite bridge gap filling material comprises the following steps:
[0046] Room temperature shape memory piezoelectric polymer composite bridge filling material is based on (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3's polyurethane-epoxy resin-piezoelectric composite material, in this embodiment, the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin and conductive agent conductive carbon black are 5%, 94.8% and 0.2% respectively.
[0047] S1. Preparation of epoxy resin precursor: Under nitrogen atmosphere, epoxy resin and 2,2'-diaminodiphenyl disulfide are weighed in a molar ratio of epoxy group to amino group of 2:1, heated to 110°C in a four-necked flask, and mechanically stirred at a rate of 600 r / min for 4 hours to obtain a viscous solution, which is an epoxy resin precursor; wherein the epoxy resin is bisphenol A epoxy resin, model E51.
[0048] S2. Preparation of polyurethane prepolymer: Under a nitrogen atmosphere, 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide were weighed and mixed in a molar ratio of 3:1:2, heated to 110° C., and mechanically stirred at a rate of 600 r / min for 4 h to obtain a thermoplastic polyurethane prepolymer.
[0049] S3. Preparation of polyurethane-epoxy resin: Mix the thermoplastic polyurethane prepolymer of step S2 with the epoxy resin precursor of step S1, the mass percentages of the thermoplastic polyurethane prepolymer and the epoxy resin precursor are 55% and 45% respectively, heat to 110°C under a nitrogen atmosphere, and mechanically stir at a rate of 800 r / min for 6 hours to obtain a uniform polyurethane-epoxy resin.
[0050] S4. Preparation of piezoelectric ceramic materials: According to the molecular formula (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 in a stoichiometric ratio: weigh the raw materials separately, mix them evenly, add agate balls and anhydrous ethanol, and ball mill for 12 hours, then separate the agate balls, dry them at 70°C for 12 hours, and pass them through a 120-mesh sieve to obtain a raw material mixture; the raw materials are BaCO3, Li2CO3, Al2O3, CaCO3, ZrO2 and TiO2; the usage ratio of the raw material mixture, agate balls and anhydrous ethanol is 0.40g:1g:0.60mL.
[0051] The raw material mixture was pre-calcined at 1200° C. for 6 h and naturally cooled to room temperature to obtain pre-calcined powder I.
[0052] Agate balls and anhydrous ethanol were added to the pre-burned powder I, and the mixture was ball-milled for a second time for 12 hours. After the agate balls were separated, the mixture was dried at 70°C for 12 hours and passed through a 120-mesh sieve to obtain pre-burned powder II with a particle size of 0.125 mm. The dosage ratio of the pre-burned powder I, the agate balls and the anhydrous ethanol was 0.30 g:1 g:0.40 mL. The mass of the agate balls was matched according to the ratio of 10 mm:5 mm:2 mm in diameter = 3:2:1.
[0053] The pre-sintered powder II was polarized at room temperature and in a direct current electric field of 1 kV / cm for 30 minutes to obtain a piezoelectric ceramic material.
[0054] S5. Preparation of polyurethane-epoxy resin-piezoelectric composite material: add the piezoelectric ceramic material and conductive carbon black of step S4 into the polyurethane-epoxy resin of step S3, and mechanically stir at 800 r / min for 6 hours at 110°C to obtain a uniformly mixed black viscous liquid; wherein the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin, and conductive carbon black are 5%, 94.8%, and 0.2%, respectively.
[0055] Casting: pouring the black viscous liquid in step S5 into a preheated polytetrafluoroethylene mold to obtain a polyurethane-epoxy resin-piezoelectric composite material casting body, the size of the polyurethane-epoxy resin-piezoelectric composite material casting body is 160×20×1 mm.
[0056] Curing: The polyurethane-epoxy resin-piezoelectric composite material casting was placed in a vacuum oven for degassing to completely eliminate bubbles, and then heated to 60°C in the vacuum oven at a heating rate of 5°C / min for aging for 24 hours, and then heated to 100°C at a heating rate of 5°C / min for curing for 8 hours, and then cooled to room temperature to obtain a room temperature shape memory piezoelectric polymer composite bridge filling material.
[0057] The shape memory performance of the room temperature shape memory piezoelectric polymer composite bridge caulking material (the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin, and conductive carbon black are 5%, 94.8%, and 0.2%, respectively) prepared in Example 1 was tested at room temperature 25°C, 1.5kPa static load, and static and dynamic load. The test method is: the room temperature shape memory piezoelectric polymer composite bridge caulking material of Example 1 is heated to 60°C, then folded in half by applying external force and cooled to 0°C, and its temporary shape is fixed and maintained for 5 minutes. Finally, the folded room temperature shape memory piezoelectric polymer composite bridge caulking material is placed at a static water depth of 15cm. According to p=ρgh, the pressure of the room temperature shape memory piezoelectric polymer composite bridge caulking material in water is 1.5kPa at this time. The shape memory recovery performance is observed under the action of no ultrasound (static load) and ultrasound with a power of 40kHz (static and dynamic load). The test results are shown in Table 1.
[0058] Table 1: Restoration angle and restoration rate of Example 1
[0059]
[0060] The results in Table 1 show that the shape memory recovery rate of the prepared shape memory piezoelectric polymer composite bridge filling material can reach 58.83% and 66.67% within 1 minute under static load and static and dynamic load at 25°C and 1.5 kPa, which can effectively alleviate the problem of insufficient adaptive bridge deformation ability of room temperature shape memory piezoelectric polymer composite bridge filling materials at room temperature.
[0061] Example 2
[0062] A method for preparing a room temperature shape memory piezoelectric polymer composite bridge gap filling material comprises the following steps:
[0063] Room temperature shape memory piezoelectric polymer composite bridge filling material is based on (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15)(Zr 0.1 Ti 0.9 )O3's polyurethane-epoxy resin-piezoelectric composite material, in this embodiment, the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin and conductive agent conductive carbon black are 10%, 89.6% and 0.4% respectively.
[0064] S1. Preparation of epoxy resin precursor: Under nitrogen atmosphere, epoxy resin and 2,2'-diaminodiphenyl disulfide are weighed in a molar ratio of epoxy group to amino group of 2:1, heated to 120°C in a four-necked flask, and mechanically stirred at a rate of 500 r / min for 4 hours to obtain a viscous solution, which is an epoxy resin precursor; wherein the epoxy resin is bisphenol A epoxy resin, model E51.
[0065] S2. Preparation of polyurethane prepolymer: Under nitrogen atmosphere, 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide were weighed and mixed in a molar ratio of 3:1:2, heated to 120° C., and mechanically stirred at a rate of 500 r / min for 4 h to obtain a thermoplastic polyurethane prepolymer;
[0066] S3. Preparation of polyurethane-epoxy resin: Mix the thermoplastic polyurethane prepolymer of step S2 with the epoxy resin precursor of step S1, the mass percentages of the thermoplastic polyurethane prepolymer and the epoxy resin precursor are 58% and 42% respectively, heat to 120°C under a nitrogen atmosphere, and mechanically stir at a rate of 500 r / min for 4 hours to obtain a uniform polyurethane-epoxy resin.
[0067] S4. Preparation of piezoelectric ceramic materials: According to the molecular weight (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 in a stoichiometric ratio: weigh the raw materials separately, mix them evenly, add agate balls and anhydrous ethanol, ball mill for 20 hours, separate the agate balls, dry them at 75°C for 12 hours, and pass them through a 120-mesh sieve to obtain a raw material mixture; the raw materials are BaCO3, Li2CO3, Al2O3, CaCO3, ZrO2 and TiO2; the dosage ratio of the raw material mixture, agate balls and anhydrous ethanol is 0.40g:1g:0.60mL.
[0068] The raw material mixture was pre-calcined at 1250° C. for 5 h and naturally cooled to room temperature to obtain pre-calcined powder I.
[0069] Agate balls and anhydrous ethanol were added to the pre-burned powder I, and the mixture was ball-milled for a second time for 20 hours. After the agate balls were separated, the mixture was dried at 75°C for 12 hours and passed through a 250-mesh sieve to obtain pre-burned powder II with a particle size of 0.062 mm. The dosage ratio of the pre-burned powder I, the agate balls and the anhydrous ethanol was 0.30 g:1 g:0.40 mL. The mass of the agate balls was matched according to the ratio of 10 mm:5 mm:2 mm in diameter = 3:2:1.
[0070] The pre-sintered powder II was polarized at room temperature under a direct current electric field of 3 kV / cm for 10 min to obtain a piezoelectric ceramic material.
[0071] S5. Preparation of polyurethane-epoxy resin-piezoelectric composite material: add the piezoelectric ceramic material and conductive carbon black of step S4 into the polyurethane-epoxy resin of step S3, and mechanically stir at 120°C and a rate of 600 r / min for 4 hours to obtain a uniformly mixed black viscous liquid; wherein the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin, and conductive carbon black are 10%, 89.6%, and 0.4%, respectively.
[0072] Casting: pouring the black viscous liquid in step S5 into a preheated polytetrafluoroethylene mold to obtain a polyurethane-epoxy resin-piezoelectric composite material casting body, the size of the polyurethane-epoxy resin-piezoelectric composite material casting body is 160×20×1 mm.
[0073] Curing: The polyurethane-epoxy resin-piezoelectric composite casting was placed in a vacuum oven for degassing to completely eliminate bubbles, and then the temperature was raised to 80°C at a heating rate of 8°C / min in the vacuum oven for aging for 12 hours, and then the temperature was raised to 120 at a heating rate of 8°C / min for curing for 6 hours, and then cooled to room temperature to obtain a room temperature shape memory piezoelectric polymer composite bridge filling material.
[0074] The shape memory performance of the room temperature shape memory piezoelectric polymer composite bridge caulking material (the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin, and conductive carbon black are 10%, 89.6%, and 0.4%, respectively) prepared in Example 2 was tested at room temperature 30°C, 1.5kPa static load, and static and dynamic load. The test method is: the room temperature shape memory piezoelectric polymer composite bridge caulking material of Example 2 is heated to 60°C, then folded in half by applying external force and cooled to 0°C, and its temporary shape is fixed and maintained for 5 minutes. Finally, the folded room temperature shape memory piezoelectric polymer composite bridge caulking material is placed at a still water depth of 15cm. According to p=ρgh, the pressure of the room temperature shape memory piezoelectric polymer composite bridge caulking material in water is 1.5kPa at this time. The shape memory recovery performance is observed under the action of no ultrasound (static load) and ultrasound with a power of 40kHz (static and dynamic load). The test results are shown in Table 2.
[0075] Table 2: Restoration angle and restoration rate of Example 2
[0076]
[0077] The results in Table 2 show that the shape memory recovery rate of the prepared shape memory piezoelectric polymer composite bridge filling material can reach 47.22% and 66.67% within 1 minute under static load and static and dynamic load at 30°C and 1.5 kPa, which can effectively alleviate the problem of insufficient adaptive bridge deformation ability of room temperature shape memory piezoelectric polymer composite bridge filling materials at room temperature.
[0078] Example 3
[0079] A method for preparing a room temperature shape memory piezoelectric polymer composite bridge gap filling material comprises the following steps:
[0080] Room temperature shape memory piezoelectric polymer composite bridge filling material is based on (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3's polyurethane-epoxy resin-piezoelectric composite material, the mass percentages of the piezoelectric ceramic material, polyurethane-epoxy resin, and conductive agent conductive carbon black are 20%, 79.5%, and 0.5%, respectively.
[0081] S1. Preparation of epoxy resin precursor: Under nitrogen atmosphere, epoxy resin and 2,2'-diaminodiphenyl disulfide are weighed in a molar ratio of epoxy group to amino group of 2:1, heated to 125°C in a four-necked flask, and mechanically stirred at a rate of 400 r / min for 3 h to obtain a viscous solution, which is an epoxy resin precursor; wherein the epoxy resin is bisphenol A epoxy resin, model E51.
[0082] S2. Preparation of polyurethane prepolymer: Under a nitrogen atmosphere, 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide were weighed and mixed in a molar ratio of 3:1:2, heated to 125°C, and mechanically stirred at a rate of 400 r / min for 3 hours to obtain a thermoplastic polyurethane prepolymer.
[0083] S3. Preparation of polyurethane-epoxy resin: Mix the thermoplastic polyurethane prepolymer of step S2 with the epoxy resin precursor obtained in step S1, the mass percentages of the thermoplastic polyurethane prepolymer and the epoxy resin precursor being 60% and 40% respectively; heat to 125° C. under a nitrogen atmosphere, and mechanically stir at a rate of 500 r / min for 5 hours to obtain a uniform polyurethane-epoxy resin.
[0084] S4. Preparation of piezoelectric ceramic materials: According to the molecular formula (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 stoichiometric ratio: weigh the raw materials respectively, mix them evenly, add agate balls and anhydrous ethanol, ball mill for 18 hours, separate the agate balls, dry them at 80°C for 10 hours, and pass them through a 120-mesh sieve to obtain a raw material mixture; the raw materials are BaCO3, Li2CO3, Al2O3, CaCO3, ZrO2 and TiO2; the usage ratio of the raw material mixture, agate balls and anhydrous ethanol is 0.40g:1g:0.60mL;
[0085] The raw material mixture was pre-calcined at 1200° C. for 5 h and naturally cooled to room temperature to obtain pre-calcined powder I.
[0086] Agate balls and anhydrous ethanol were added to the pre-burned powder I, and the mixture was ball-milled for a second time for 18 hours. After the agate balls were separated, the mixture was dried at 80°C for 10 hours and passed through a 200-mesh sieve to obtain pre-burned powder II with a particle size of 0.075 mm. The dosage ratio of the pre-burned powder I, the agate balls and the anhydrous ethanol was 0.30 g:1 g:0.40 mL. The mass of the agate balls was matched according to the ratio of 10 mm:5 mm:2 mm in diameter = 3:2:1.
[0087] The pre-sintered powder II was polarized at room temperature under a direct current electric field of 2 kV / cm for 20 min to obtain a piezoelectric ceramic material.
[0088] S5. Preparation of polyurethane-epoxy resin-piezoelectric composite material: add the piezoelectric ceramic material and conductive carbon black of step S4 into the polyurethane-epoxy resin of step S3, and mechanically stir at 125°C and 500 r / min for 5 hours to obtain a uniformly mixed black viscous liquid; wherein the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin and conductive carbon black are 20%, 79.5% and 0.5% respectively.
[0089] Casting: pouring the black viscous liquid in step S5 into a preheated polytetrafluoroethylene mold to obtain a polyurethane-epoxy resin-piezoelectric composite material casting body, the size of the polyurethane-epoxy resin-piezoelectric composite material casting body is 160×20×1 mm.
[0090] Curing: The polyurethane-epoxy resin-piezoelectric composite casting was placed in a vacuum oven for degassing to completely eliminate bubbles, and then the temperature was raised to 70°C at a heating rate of 6°C / min in the vacuum oven for aging for 18 hours, and then the temperature was raised to 125 at a heating rate of 6°C / min for curing for 5 hours, and then cooled to room temperature to obtain a room temperature shape memory piezoelectric polymer composite bridge filling material.
[0091] The shape memory performance of the room temperature shape memory piezoelectric polymer composite bridge caulking material (the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin, and conductive carbon black are 20%, 79.5%, and 0.5%, respectively) prepared in Example 3 was tested at room temperature 30°C, 1.5kPa static load and static and dynamic load. The test method is: the room temperature shape memory piezoelectric polymer composite bridge caulking material of Example 3 is heated to 60°C, then folded in half by applying external force and cooled to 0°C, fixed its temporary shape and maintained for 5 minutes, and finally the folded room temperature shape memory piezoelectric polymer composite bridge caulking material is placed at a static water depth of 15cm. According to p=ρgh, the pressure of the room temperature shape memory piezoelectric polymer composite bridge caulking material in water is 1.5kPa at this time, and its shape memory recovery performance is observed under the action of no ultrasound (static load) and ultrasound with a power of 40kHz (static and dynamic load). The test results are shown in Table 3.
[0092] Table 3: Restoration angle and restoration rate of Example 3
[0093]
[0094] The results in Table 3 show that the shape memory recovery rate of the prepared shape memory piezoelectric polymer composite bridge filling material can reach 50% and 67.78% within 1 minute under static load and static and dynamic load at 30°C and 1.5kPa, which can effectively improve the problem of insufficient adaptive bridge deformation ability of room temperature shape memory piezoelectric polymer composite bridge filling materials at room temperature.
[0095] Example 4
[0096] A method for preparing a room temperature shape memory piezoelectric polymer composite bridge gap filling material comprises the following steps:
[0097] Room temperature shape memory piezoelectric polymer composite bridge filling material is based on (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3's polyurethane-epoxy resin-piezoelectric composite material, the mass ratios of the piezoelectric ceramic material, polyurethane-epoxy resin, and conductive agent conductive carbon black are 40%, 59.2%, and 0.8%, respectively.
[0098] S1. Preparation of epoxy resin precursor: Under nitrogen atmosphere, epoxy resin and 2,2'-diaminodiphenyl disulfide are weighed in a molar ratio of epoxy group to amino group of 2:1, heated to 130°C in a four-necked flask, and mechanically stirred at a rate of 300 r / min for 2 h to obtain a viscous solution, which is an epoxy resin precursor; wherein the epoxy resin is bisphenol A epoxy resin, model E51.
[0099] S2. Preparation of polyurethane prepolymer: Under a nitrogen atmosphere, 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide were weighed and mixed in a molar ratio of 3:1:2, heated to 130° C., and mechanically stirred at a rate of 300 r / min for 2 h to obtain a thermoplastic polyurethane prepolymer.
[0100] S3. Preparation of polyurethane-epoxy resin: Mix the thermoplastic polyurethane prepolymer of step S2 with the epoxy resin precursor obtained in step S1, the mass percentages of the thermoplastic polyurethane prepolymer and the epoxy resin precursor are 65% and 35% respectively, heat to 130°C under a nitrogen atmosphere, and mechanically stir at a rate of 400 r / min for 2 hours to obtain a uniform polyurethane-epoxy resin.
[0101] S4. Preparation of piezoelectric ceramic materials: According to the molecular formula (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 in a stoichiometric ratio: weigh the raw materials separately, mix them evenly, add agate balls and anhydrous ethanol, ball mill for 24 hours, separate the agate balls, dry them at 80°C for 10 hours, and pass them through a 120-mesh sieve to obtain a raw material mixture; the raw materials are BaCO3, Li2CO3, Al2O3, CaCO3, ZrO2 and TiO2; the dosage ratio of the raw material mixture, agate balls and anhydrous ethanol is 0.40g:1g:0.60mL.
[0102] The raw material mixture was pre-calcined at 1250° C. for 4 h and naturally cooled to room temperature to obtain pre-calcined powder I.
[0103] Agate balls and anhydrous ethanol were added to the pre-burned powder I, and the mixture was ball-milled for a second time for 24 hours. After the agate balls were separated, the mixture was dried at 80°C for 10 hours and passed through a 250-mesh sieve to obtain pre-burned powder II with a particle size of 0.062 mm. The dosage ratio of the pre-burned powder I, the agate balls and the anhydrous ethanol was 0.30 g:1 g:0.40 mL. The mass of the agate balls was matched according to the ratio of 10 mm:5 mm:2 mm in diameter = 3:2:1.
[0104] The pre-sintered powder II was polarized at room temperature under a direct current electric field of 3 kV / cm for 10 min to obtain a piezoelectric ceramic material.
[0105] S5. Preparation of polyurethane-epoxy resin-piezoelectric composite material: add the piezoelectric ceramic material and conductive carbon black of step S4 into the polyurethane-epoxy resin of step S3, and mechanically stir at 130°C and 400 r / min for 2 hours to obtain a uniformly mixed black viscous liquid; wherein the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin, and conductive carbon black are 40%, 59.2%, and 0.8%, respectively.
[0106] Casting: pouring the black viscous liquid in step S5 into a preheated polytetrafluoroethylene mold to obtain a polyurethane-epoxy resin-piezoelectric composite material casting body, the size of the polyurethane-epoxy resin-piezoelectric composite material casting body is 160×20×1 mm.
[0107] Curing: The polyurethane-epoxy resin-piezoelectric composite material casting was placed in a vacuum oven for degassing to completely eliminate bubbles, and then the temperature was raised to 90°C in the vacuum oven at a heating rate of 10°C / min for aging for 10 hours, and then the temperature was raised to 130°C at a heating rate of 10°C / min for curing for 4 hours, and then cooled to room temperature to obtain a room temperature shape memory piezoelectric polymer composite bridge filling material.
[0108] The shape memory performance of the room temperature shape memory piezoelectric polymer composite bridge caulking material (the mass percentages of piezoelectric ceramic material, polyurethane-epoxy resin, and conductive carbon black are 40%, 59.2%, and 0.8%, respectively) prepared in Example 4 was tested at room temperature 30°C, 1.5kPa static load, and static and dynamic load. The test method is: the room temperature shape memory piezoelectric polymer composite bridge caulking material of Example 4 is heated to 60°C, then folded in half by applying external force and cooled to 0°C, and its temporary shape is fixed and maintained for 5 minutes. Finally, the folded room temperature shape memory piezoelectric polymer composite bridge caulking material is placed at a static water depth of 15cm. According to p=ρgh, the pressure of the room temperature shape memory piezoelectric polymer composite bridge caulking material in water is 1.5kPa at this time. The shape memory recovery performance is observed under the action of no ultrasound (static load) and ultrasound with a power of 40kHz (static and dynamic load). The test results are shown in Table 4.
[0109] Table 4: Restoration angle and restoration rate of Example 4
[0110]
[0111] The results in Table 4 show that the shape memory recovery rate of the prepared shape memory piezoelectric polymer composite bridge filling material can reach 55.56% and 69.44% within 1 minute under static load and static and dynamic load at 30°C and 1.5 kPa, which can effectively solve the problem of insufficient adaptive bridge deformation ability of room temperature shape memory piezoelectric polymer composite bridge filling materials at room temperature.
[0112] Figure 1 The XRD patterns of the polyurethane-epoxy resin-piezoelectric composite materials prepared in Examples 1 to 4 of the present invention are shown in FIG. Figure 1 It can be seen that the room temperature shape memory piezoelectric polymer composite bridge filling materials prepared in Examples 1 to 4 all have obvious crystalline phase regions and amorphous phase regions. In the amorphous phase region: a broad diffraction peak at 14.08° indicates that there is an amorphous diffraction peak in the polyurethane-epoxy resin-piezoelectric composite material, and the scattering at 14.08° is attributed to the scattering of the hard segment phase in the thermoplastic polyurethane prepolymer; in the crystalline phase region: sharp diffraction peaks, such as at 31° and 38°, refer to (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 ceramic diffraction peak. It shows that piezoelectric phase ceramics (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 and conductive carbon black are evenly distributed in the matrix polymer polyurethane-epoxy resin to form a uniform and stable system. The existence of the crystalline phase region helps the shape fixing property, while the amorphous phase region can promote the shape recovery property.
[0113] Figure 2 The infrared spectra of the polyurethane-epoxy resin-piezoelectric composite materials prepared in Examples 1 to 4 of the present invention are shown in FIG. Figure 2 It can be seen that in the room temperature shape memory piezoelectric polymer composite bridge filling materials prepared in Examples 1 to 4, there is no obvious chemical interaction between polyurethane-epoxy resin and piezoelectric phase ceramics, and all polyurethane-epoxy resins, piezoelectric phase ceramics and polyurethane-epoxy resin-piezoelectric composite materials have almost the same profiles, and there is no obvious change in the infrared spectrum, so there is no obvious chemical interaction.
[0114] There is a certain bonding effect between polyurethane-epoxy resin and conductive carbon black, which can be seen from the infrared spectrum at 1700cm -1 and 1730cm -1The change in the intensity of the diffraction peak at shows that the bonding action includes hydrogen bonding. The presence of hydrogen bonding is conducive to improving the interface connection between the conductive carbon black and the polyurethane-epoxy resin. In addition, since the conductive carbon black, thermoplastic polyurethane prepolymer and epoxy resin precursor can all generate hydrogen bonds, the presence of hydrogen bonding is likely to promote the aggregation of hard segments, resulting in microphase separation between hard segments and soft segments, thereby enhancing shape memory properties and mechanical properties.
[0115] Combining Table 4 and Figure 3 It is concluded that piezoelectric phase ceramics (Ba 0.83 Li 0.01 Al 0.01 Ca 0.15 )(Zr 0.1 Ti 0.9 The piezoelectric effect provided by )O3 is conducive to promoting the shape memory recovery of polyurethane-epoxy resin-piezoelectric composite materials. The principle is: this may be due to the huge pressure of the driving load stimulating the piezoelectric activity of the polyurethane-epoxy resin-piezoelectric composite material and generating a large amount of electrical energy. With the help of conductive fillers, the electrical energy will be converted into heat energy in large quantities, which will then soften the hard phase and increase the rate of disulfide bond exchange, contributing to the shape memory.
[0116] Figure 4 This is a diagram of the self-repairing performance of the room temperature shape memory piezoelectric polymer composite bridge gap filling material prepared in Example 4 of the present invention. The self-repairing test method is: scratch a 92px wide scratch on the surface of the room temperature shape memory piezoelectric polymer composite bridge gap filling material of Example 4, then heat it at 80°C, and observe the change in the width of the scratch within 15 minutes to monitor its self-repairing performance. The results show that the repair rate within 15 minutes at 80°C is 30.5%, and the repair rate = 64 / 92×100%.
[0117] via Figure 5 It can be seen that the piezoelectric constant d33 of the piezoelectric ceramic material can reach 448pC / N at room temperature, and its depolarization temperature can reach 85℃-95℃. The ceramic will not depolarize and fail within the temperature range of the bridge expansion joint.
[0118] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A method for preparing a room temperature shape memory piezoelectric polymer composite bridge filling material, characterized in that: The steps include: In a nitrogen atmosphere, after epoxy resin and 2,2'-diaminodiphenyl disulfide are mixed, the amino group of 2,2'-diaminodiphenyl disulfide and the epoxy group of the epoxy resin undergo a ring-opening reaction to obtain an epoxy resin precursor; In a nitrogen atmosphere, 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide are mixed, and then prepolymerized and chain-extended to obtain a thermoplastic polyurethane prepolymer; In a nitrogen atmosphere, an epoxy resin precursor and a thermoplastic polyurethane prepolymer are mixed so that the molecular chains of the epoxy resin precursor and the thermoplastic polyurethane prepolymer penetrate each other to obtain a polyurethane-epoxy resin having an interpenetrating network structure; According to the chemical formula (Ba 0.85-2x Li x Al x Ca 0.15 )(Zr 0.1 Ti 0.9 )O3 weigh a Ba source, a Li source, an Al source, a Ca source, a Zr source and a Ti source, and mix them to obtain a raw material mixture, wherein 0<x<0.3; The raw material mixture is pre-sintered and then polarized for 10-30 minutes under a DC electric field of 1 kV / cm-3 kV / cm to orient the internal electric domains to obtain a piezoelectric ceramic material with piezoelectric properties; The piezoelectric ceramic material, polyurethane-epoxy resin and conductive agent are mixed, and then cast and cured to obtain a room temperature shape memory piezoelectric polymer composite bridge filling material; the piezoelectric ceramic material generates electric charge under the action of external stress, and the conductive agent converts the electrical energy into thermal energy. Under the action of thermal energy, the dynamic covalent disulfide bonds of the polyurethane-epoxy resin undergo a dynamic exchange reaction, and the dynamic covalent disulfide bonds are broken, decomposed and reorganized, and then shape memory recovery occurs.
2. The method for preparing a room temperature shape memory piezoelectric polymer composite bridge filling material according to claim 1, characterized in that: The conditions for the ring-opening reaction are: heating and stirring at 110°C-130°C for 2h-4h.
3. The method for preparing a room temperature shape memory piezoelectric polymer composite bridge filling material according to claim 1, characterized in that: The molar ratio of the epoxy group in the epoxy resin to the amino group in the 2,2'-diaminodiphenyl disulfide is 1.9-2.0:
1.
4. The method for preparing a room temperature shape memory piezoelectric polymer composite bridge filling material according to claim 1, characterized in that: The conditions for the prepolymerization and chain extension reactions are: heating and stirring at 110°C-130°C for 2h-4h.
5. The method for preparing a room temperature shape memory piezoelectric polymer composite bridge gap filling material according to claim 1, characterized in that: The molar ratio of 4,4-diphenylmethane diisocyanate, polyether polyol and 2,2'-diaminodiphenyl disulfide is 3:1:1.8-2.
6. The method for preparing a room temperature shape memory piezoelectric polymer composite bridge filling material according to claim 1, characterized in that: The mass percentages of the polyurethane prepolymer and the epoxy resin precursor are 55%-65% and 35%-45% respectively, and the sum of the mass percentages of the two is 100%.
7. The method for preparing a room temperature shape memory piezoelectric polymer composite bridge gap filling material according to claim 1, characterized in that: The raw material mixture is pre-calcined at 1200°C-1250°C for 4h-6h to obtain pre-calcined powder I, and the pre-calcined powder I is ball-milled to obtain pre-calcined powder II with a particle size of 0.062mm-0.125mm, and the pre-calcined powder II is polarized under a DC electric field of 1kV / cm-3kV / cm for 10min-30min.
8. The method for preparing a room temperature shape memory piezoelectric polymer composite bridge gap filling material according to claim 1, characterized in that: The mass percentages of the piezoelectric ceramic material, the polyurethane-epoxy resin and the conductive agent are 5%-40%, 59.2%-94.8% and 0.2%-0.8% respectively, and the sum of the mass percentages of the three is 100%.
9. A room temperature shape memory piezoelectric polymer composite bridge filling material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Room temperature shape memory piezoelectric polymer composite bridge filling material has shape memory properties at room temperature.
10. Use of the room temperature shape memory piezoelectric polymer composite bridge filling material according to claim 9 in the preparation of bridge filling materials.
Citation Information
Patent Citations
Polyurethane-base piezoelectric conductive intelligent composite damping material and preparation method thereof
CN103289363A
Elastomer matrix broadband high-damping composite material taking three-dimensional carbon framework as conductive phase and preparation method of material
CN107129675A
Piezoelectric ceramic material with high voltage electric response and high Curie temperature and preparation method thereof
CN109626988A
Polyurethane / epoxy resin blend with shape memory, self-repairing and recyclability functions and preparation method thereof
CN110305466A
Preparation method of leadless piezoelectric ceramic material
CN111635229A
Cited By
Preparation method of titanium alloy anti-corrosion self-repairing intelligent coating used in marine environment
CN120005484A